Ferroelastic Phase Transition In Some Phenols-Amines Adducts – Experimental And Theoretical Findings. - Fun, H.K.; Chantrapromma, Asistant Professor Suchada; How, P.T. (2004)
A new type of structural phase transition has been discovered recently in a class of hydrogen-bonded organic crystals.